O ultraneoliberalismo e a correlação de forças entre o agronegócio e a agricultura familiar - Souza, Maria Aléxcia Michelle.F.de Lima (2023)
The current hostile scenario of ultraneoliberalism brings us an image of a lag of family farming in relation to the hegemony of agribusiness and its large exports, based on these issues we will allow us to capture the effects of the transition to ultraneoliberalism on the discrepancies between family farming and the agribusiness, based on a critical comparison of the 2006 and 2017 Agricultural Censuses and scientific literature. The need to promote this debate was generated due to a certain shortage in Social Work, and we can raise discourse flags so that there is an effective insertion of the debate on the Agrarian Question in the professional training of Social Workers. We adopted the Critical Social Theory to guide us along this path, together with bibliographical and documentary research through the IBGE Agricultural Censuses. In this research, we built a theoretical approach divided into three chapters, ranging from the expropriations in primitive accumulation, moving towards the constitutive aspects of the Brazilian social formation, as well as approaching the conceptual distinctions and correlations of force that involve the two forms of production and, finally, the data analysis through indicators, such as the number of agricultural establishments, pesticides and land concentration, we were able to observe that family farming is rooted in the agricultural sector, providing food for consumption by Brazilians in a sustainable and egalitarian way.